Analisis Bakteri Coliform Pada Air Minum Isi Ulang Di Wilayah Poasia Kota Kendari - Askrening Askrening; Reni Yunus (POLTEKKES KEMENKES YOGYAKARTA, 2017)
The existence of safe drinking water now begin to be limited in number, so that the existence of refill drinking water depotbecomes an alternative water treatment process, in principle, should be able to eliminate all kinds of pollutants, includingcoliform bacteria, which is a group of bacteria used as an indicator of pollution, waste and conditions which are not good forwater. This study aims to determine coliform bacteria contamination in refill drinking water depot in Poasia Kendari. The typeof research is descriptive analytic approach using MPN (Most Probable Number). These samples included 10 samples takenwith saturated total sampling method. Data were analyzed by using frequency distribution. The results showed that thesamples were positive in getting as much as 6 samples (60%) and over the limit contamination and negative samples ingetting as many as four samples (40%), so it can be concluded that from coliform bacteria identification of 10 samples of refilldrinking water in Poasia Kendari, 6 samples were identified contaminated with coliform bacteria and microbial contaminationwas over the limit of PERMENKES 492 / Menkes / Per / IV.2010.